Competence of Social Attitudes at Madrasah Ibtidaiyah: A Science Learning Model Based on Social Intelligence from an Islamic Perspective: Kompetensi Sikap Sosial di Madrasah Ibtidaiyah: Model Pembelajaran Sains Berbasis Kecerdasan Sosial Perspektif Islam - Faliyandra, Faisal (Universitas Muhammadiyah Sidoarjo, 2021)
The destruction of natural and human resources is caused by an imbalance between good relations with Allah SWT (vertical) and between humans (horizontally). The Islamic perspective of social intelligence bridges the imbalance of two dimensions that are related well according to Islam (Hablum Minannas and Hablum Minallah). This study aimed to analyze the need for an integrated science learning process with social intelligence from an Islamic perspective. The research approach used is qualitative with a needs analysis. This study involved 8 teachers spread across MI Thoriqun Najah and MI Nurul Huda Kapongan Situbondo. Data was collected through literature study, interviews, and documentation. The results of the study stated that 1) the teacher's desire to integrate science learning and social intelligence with an Islamic perspective, 2) There are ten basic competencies which are derived from the core competencies of social attitudes (KI-2), which can be integrated into science learning based on social intelligence from an Islamic perspective. This depends on the creativity of the teacher in seeking innovative learning, 3) The most effective method used for learning science-based on social intelligence from an Islamic perspective is the group and demonstration model, 4) Relevant scoring systems can be used for assessment in the social intelligence-based science learning process. Islamic perspective, namely non-test with questionnaires, performance appraisal observations, and portfolios.